Swarming microbombyliids (Diptera, Mythicomyiidae) in amber from Ukraine: a new species and a new synonymy - Perkovsky, Evgeny E.; Sun, Haoran; Perkovsky, Alisa A.; Pape, Thomas (Zootaxa, 2025)
Mythenteles evenhuisi sp. nov. is described from Rovno amber and compared with Mythenteles baltica Evenhuis, 2002. The discovery of fourteen males of Mythenteles Hall & Evenhuis within a single Rovno amber piece, along with six specimens of Glabellula Bezzi in another amber piece, strongly suggests that swarming behavior in Mythicomyiidae occurred as frequently in Eocene forest as observed in extant European populations. Glabellula aggregata Evenhuis, 2013 is considered a senior synonym of Glabellula perkovskyi Evenhuis, 2013 syn. nov. Localities of findings of all Eocene microbombyliids known from Ukraine and Denmark are indicated. The higher frequency of Mythicomyiidae in Rovno amber as compared to Baltic amber may indicate a greater prevalence of open, dry habitats in the Rovno amber forest.